Comparison between different strategies for the realization of flashing-light effects - Pneumatic mixing and flashing illumination - Luzi, Giovanni; McHardy, Christopher; Lindenberger, Christoph; Rauh, Cornelia; Delgado, Antonio (Algal Research, 2019)
A major limitation for the phototrophic cultivation of microalgae in photobioreactors is the low culture density which results in expensive harvesting and downstream processes. It is often mentioned that intensive mixing of the culture can improve the efficiency of light utilization by realizing flashing-light effects which enhance the growth of cell cultures. Alternatively, flashing light sources could provide a way to realize this effect without the need of supplying additional energy for fast mixing. While the effects of mixing have been investigated at various reactor scales, experiments with flashing illumination have been mostly conducted in small geometries. In addition, few studies have been conducted for photobioreactors with larger light paths, being characteristic for the production scale. By means of numerical simulations, we evaluate pneumatic mixing and flashing illumination with regard to their ability to realize flashing-light effects in a 5 cm diameter bubble column filled with a suspension of Chlamydomonas reinhardtii. To the best of our knowledge, a numerical comparison between the effects of flashing illumination and pneumatic mixing on the culture growth has not been reported in literature.
CRIS-Team WoS Importer:2019-02-22